A case of nasopharyngeal clear cell carcinoma diagnosed by molecular analysis. Issue 1 (1st January 2018) - Hara, Makiko; Otsuki, Naoki; Yanagisawa, Shungaku; Kokan, Norio; Fujio, Hisami; Shinomiya, Hitomi; Morita, Naruhiko; Hara, Shigeru; Inagaki, Hiroshi; Nibu, Ken-Ichi
Abstract: Clear cell carcinoma (CCC) in the salivary gland is a rare malignant neoplasm and is hardly located in the nasopharynx. An 18-year-old female presented with a 3-year history of nasal congestion. Endoscopic examination revealed a reddish round-shaped mass with a smooth surface in the posterior wall of the nasopharynx. An en bloc resection of the tumor was performed by endoscopic surgery. Preliminary pathological diagnosis made by histopathological examination was mucoepidermoid carcinoma. However, FISH analysis for MAML2-split was negative but that for EWSR1-split was positive. In addition, EWSR1-ATF1 fusion transcript was detected in the RT-PCR analysis. The final pathological diagnosis of CCC was made on the basis of these findings. Since EWSR1-ATF1 fusion is not observed in other salivary gland tumors, identifications of this unique fusion gene by FISH and RT-PCR are useful tools to confirm the diagnosis of CCC.